Makna Syahadat Payung dalam Tradisi Tarekat Asy-Syahadatain - Ilham Bustomi; Ahmad Asmuni; Naila Farah; Rifqi Ulinnuha (Journal of Religion and Social Transformation, 2023)
The shahada has an important meaning for followers of the Asy-Syahadatain order because the shahada sentence is an identity that has been attached and is rooted in this tarekat and is one of the treasures of Sufism in Indonesia. For a long time, this bond has made the creed a special study and teaching for them. One of the practices that most characterize this tarekat is the teachings of the Syahadat Payung. This research focuses on the meaning of the Syahadat Payung in the teachings of the Asy-Syahadatain tarekat. The method used is qualitative by using a literature study approach and in-depth interviews with informants. The literature study itself is intended to analyze aurod texts which are the main source about the Asy-Syahadatain order or the results of previous research as material objects, then complemented by conducting in-depth interviews with figures or leaders in the tarekat as the formal object. The results of this study found that the shahadat payung is one of the teachings of the Asy-Syahadatain congregation which has the function of protecting its congregation from polytheism, distress, and other negative things. In addition, there is a difference between the shahada payung and the ordinary shahada, namely the addition of sentence readings to the shahada. If the usual shahada only contains two sentences of shahada. Meanwhile, the shahadat payung is preceded by reciting the Salawat creed and continuing to read the shahadat payung in which there is praise or tawassul to Abah Umar which contains nicknames and titles given by one of them directly to the Prophet Muhammad.